A tale of two cities: Judgments about earthquake and aftershock probabilities across time windows. (December 2015) - McClure, John; H. Doyle, Emma E.; Velluppillai, Justin M.
Abstract: Research has shown that people often misinterpret probabilities reported by experts in the media. Previous research has found that people who are given a certain probability of a volcano eruption in a specific time window judge risk as higher in later time intervals within that window. The present study examines whether a similar pattern occurs with earthquakes and aftershocks. Participants in Wellington ( N =102) and Christchurch ( N =98) in New Zealand read expert forecasts of the risk of a Wellington earthquake and a large Christchurch aftershock within specified time windows, then estimated the risk in specific intervals across the time window. Participants judged the Wellington earthquake risk as higher toward the end of the 50 year time window whereas for a Christchurch aftershock, risk estimates initially increased then plateaued. Likelihood of preparing showed a different pattern to earthquake likelihood and was constant over the time windows. These findings suggest the influence of base rates and lay theories on interpretations of scientific forecasts.